Wybrane aspekty dobrostanu psychicznego uczniów na różnych etapach edukacji. Doniesienia wstępne - Kossakowska, Karolina; Zadworna, Magdalena (Studia Edukacyjne, 2019)
Good mental health in childhood and adolescence is a prerequisite for optimal development, effective learning, build satisfying relationships with people, taking care of one’s own physical health, and self-management in adult life. Psychological well-being means life satisfaction and covers various aspects of life: school, family, friends, hobbies, etc. Thus, the status of well-being among students is vital for their psychological functioning. The aim of the present study was to identify selected aspects of the mental well-being of students at different stages of education. Study participants included fifty-nine students aged between 12 and 19 years (both males and females). The participants filled out a questionnaire concerning various aspects of life satisfaction and social functioning, designed specifically for the study. The results show that girls are more satisfied from their lives than boys, but they assess their own’s coping competencies lower than boys. Younger students show higher levels of general life satisfaction and better coping skills, although they more often have conflicting relationships with teachers. The results suggest that particular attention should be paid to older students, especially girls.